Milk Preferences of Consumers and Effect of the Marketing Mix on Consumers’ Purchase Decision of Dairy Products - Fawi, Nahid Mohammed Tawfik; Abdalla, Mohamed Osman Mohamed (Indian Journal of Marketing, 2013)
Milk and dairy products experience high consumption rates in Sudan; consumers show wide variations in their preferences for different milk types and dairy products available in the local market. Consumers’ purchase decisions are influenced by various factors. Study of such factors assists processors and producers of dairy products in implementing marketing strategies that are consumer oriented and can ultimately lead to higher selling rates. This study aimed at studying the preferences of consumption pattern of milk and factors affecting consumers’ purchase decision of dairy products in Khartoum, state capital of Sudan. Quality was found to be the main factor affecting the purchase decision, followed by price of the products. Fresh milk was the highly preferred milk type among the citizens. The study concluded with a number of recommendations, some of which are: Processors and producers of dairy products should implement modern marketing concepts that focus on the consumers’ needs and wants. Also, producers and processors should use marketing mix in ways that increases their sales and creates satisfied customers.